Duality in Vector Optimization - Jahn, Johannes (Mathematical Programming, 1983)
In this paper the problem dual to a convex vector optimization problem is defined. Under suitable assumptions, a weak, strong and strict converse duality theorem are proved. In the case of linear mappings the formulation of the dual is refined such that well-known dual problems of Gale, Kuhn and Tucker [8] and Isermann [12] are generalized by this approach. © 1983 The Mathematical Programming Society, Inc.
UnivIS-Import:2015-03-05:Pub.1983.nat.dma.pama21.dualit
Keywords: Duality; Vector Optimization